PENGUNAAN MEDIA OHV DALAM PEMBELAJARAN KOOPERATIF TOPIK TRANSFORMASI - Sehatta Saragih (Study Program of Mathematics Education of Unimed Postgraduate Program, 2008)
This study is the follow-up of previous study that showed that students’ mathematic learning output, especially in geometric topic was still low. One of the causes was strategy application that only gave little opportunity to students in building more meaningful knowledge, because strategy that was applied was not in accord with material and students characteristics. The aims of this study are to examine learning output enhancement, learning motivation and students’ activities in learning that apply The Use of Transparence Overhead Media in Cooperative Setting on Transformation Topic. The study is an experiment that took sample of 38 SMPN-1 Minas, eighth-grade students in 2005/2006 academic year. Data collections were collected by learning output test, questionnaire and class observation and then analyzed by using t-test for learning output, sign test for students motivation and descriptive test for students activities. The data analysis results show that strategies that were applied can enhance learning output, students motivation and students participation in building their knowledge.